Relationship between mandibular incisive canal and mental foramen using cone-beam computed tomography in a selected Brazilian Amazon population - Cláudia Gemaque Marinho; Pedro Luiz de Carvalho; Edson Marcos Leal Soares Ramos; Fabricio Mesquita Tuji; Nicolau Conte Neto (Revista Sul-Brasileira de Odontologia, 2018)
The mandibular canal is an anatomic structure that extends bilaterally from the mandibular foramen to the mental foramen. Objective: To identify the presence, extension, and length of the mandibular incisive canal with a cone-beam computed tomography, and to determine correlations with the positioning of the mental foramen and mandibular canal in a selected Brazilian Amazon population. Material and methods: The measurements of the incisive canal that ends at the mandible’s lower buccal and lingual border, at its initial and terminal portions, were obtained from 95 odontological examinations using cone-beam computed tomography. These measurements were compared with the measurements of the distance between the mandibular canal ending at the same cortices in 2 distinct regions at the mental foramen region. Pearson’s correlation test was used to establish a relationship between these measurements. Results: The mandibular incisive canal’s bilateral identification mean age was of 44.29 ± 11.04 y and the mean length was 10.38 ± 4.01 mm. Moderate correlations were found between the measurements of the mandibular incisive canal, mental foramen, and mandibular canal. Conclusion: The mandibular incisive canal can reach the region of the median line, and it did not present differences between the genders or for the length and distance of the mandibular incisive canal to the cortices ending at the mandible base.